Water in Architecture and its Usage in Contemporary Houses Interior Design - Sedighi, Samaneh; Mollazehi, Ali Asghar (Journal of History Culture and Art Research, 2017)
As one of the most fundamental natural elements, water has had a great share in the formation and architecture of architectural buildings. This research examines the effect of water and its presence in contemporary houses. Architecture is not merely a tridimensional compound of forms in space, but a manifestation of a sense or a thought in it. According to Feng Shui, the building where we live in can be the cause of balance and health for human being. As a whole, anything around us has active and mobile energies; by designing a building in a way that positive energies can follow around easier, one can easier bring happiness for the dwellers. Feng Shui is based on the harmony among five elements of water, wind, soil, fire and metal. Because of its stream, water removes negative energies and revives and mobilizes positive ones thereby having a great impact on the current of energies. Considering the fact that contemporary houses are small in space, designer does not feel free in the usage of water in internal spaces, thus he/she should utilize patterns that resemble or associate the feeling of water in the living environment. Conceptual, functional and aesthetic basics of water have been examined first via library studies and note taking from various papers and books. Then, the three qualities would be analyzed in Iranian architecture, and the properties of past people will be examined to emphasize material, spiritual and psychological aspects of water. Then, I will assess the philosophical basics of Feng Shui in using water for interior spaces via a qualitative method and content analysis, usage of water based on Feng Shui in interior design and decoration of homes. Considering these concepts, natural possibilities of water in interior architecture and its limitations in interior space design would be assessed and recognized. Finally, some patterns would be presented to use water in interior spaces of contemporary apartments.